1995
DOI: 10.2337/diacare.18.9.1225
|View full text |Cite
|
Sign up to set email alerts
|

Phospholipid and Glutamic Acid Decarboxylase Autoantibodies in Diabetic Neuropathy

Abstract: PLAs occur frequently in the sera of patients with diabetes and correlate with the extent of neuropathy, suggesting a role for PLAs in the etiology thereof. The measurement of PLAs may constitute a marker for ongoing damage to nerves.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 0 publications
2
26
0
Order By: Relevance
“…Studies suggest that circulating autoantibodies against motor-and sensory-nerve structures are present in the serum of patients with diabetes [158,159]. In addition, antiphospholipid antibodies (PLA) have been found in up to 88% of patients with diabetic neuropathy [160]. These antibodies are associated with a motor deficit with electrophysiologic signs of demyelination and altered nerve function.…”
Section: Autoimmune Mechanismsmentioning
confidence: 98%
“…Studies suggest that circulating autoantibodies against motor-and sensory-nerve structures are present in the serum of patients with diabetes [158,159]. In addition, antiphospholipid antibodies (PLA) have been found in up to 88% of patients with diabetic neuropathy [160]. These antibodies are associated with a motor deficit with electrophysiologic signs of demyelination and altered nerve function.…”
Section: Autoimmune Mechanismsmentioning
confidence: 98%
“…While microangiopathies and thrombotic diseases have not been convincingly associated with aPA in diabetics, there is evidence that diabetic neuropathy may be associated with aPA. Two studies [22,23] found significant increases in aPA in diabetic neuropathies, but in neither study was the PL target defined, and both investigations cite a RIA procedure as the reference for how the ELISA was performed. It appears that not much quantitative or qualitative data is available about aPA in diabetic patients, particularly in light of compelling reports that stress the importance of identifying both the type of PL [41] and its associated protein [42].…”
Section: Discussionmentioning
confidence: 99%
“…However, antibodies to phospholipid components of plasma membranes such as phosphatidylserine (aPS) and phosphatidylethanolamine (aPE) and the plasma proteins that bind to them have been described [11]. In light of the evidence of immunological and haemostatic mechanisms of endothelial and neurological damage in diabetics [1,3,6,22,24], we studied the qualitative and quantitative aspects of aPA in diabetics and asked if any of these parameters are associated with diabetic complications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that 88% of patients with diabetic neuropathy have phospholipid antibodies in their serum which correlated with sensory loss [9]. In this study we were particularly interested in neuropathy characterized by a predominance of motor features.…”
mentioning
confidence: 99%